1994
DOI: 10.1159/000263943
|View full text |Cite
|
Sign up to set email alerts
|

Beckwith-Wiedemann Syndrome: Difficulties with Prenatal Diagnosis

Abstract: Beckwith-Wiedemann syndrome (BWS), though a well-delineated clinical and morphological entity, can be difficult to diagnose by prenatal ultrasound examination when incomplete forms occur. We present a case with sonographic results including hydronephrosis, cardiomegalia, hepatomegalia, macroglossia, and prominent forehead. No abdominal wall defect was detected. Karyotype was normal. In spite of intensive prenatal diagnostics, BWS could not be diagnosed definitely until birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Numerous further signs have been occasionally described in BWS: microcephaly, facial dysmorphism, diaphragmatic hernia, cardiovascular malformations, adrenal enlargement (Nowotny et al, 1994). In our case, the striking finding was the association of omphalocoele and enlarged kidneys.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Numerous further signs have been occasionally described in BWS: microcephaly, facial dysmorphism, diaphragmatic hernia, cardiovascular malformations, adrenal enlargement (Nowotny et al, 1994). In our case, the striking finding was the association of omphalocoele and enlarged kidneys.…”
Section: Discussionsupporting
confidence: 55%
“…In some family cases of BWS, an autosomal dominant inheritance with variable expressivity and reduced penetrance has been suggested (Viljoen et al, 1991;Nowotny et al, 1994). Specific rearrangements involving chromosomal region 11p15 have been documented, and a mechanism of genomic imprinting is probably involved (Weksberg et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, even in an era of newer sonographic technology, prenatal diagnosis of the syndrome remains a rarity [2,[4][5][6][11][12][13][14][15] . Others have suggested that in the absence of maternal diabetes, an approach to the fetus with macrosomia, polyhydramnios and an enlarged placenta should include targeted ultrasound to examine for macroglossia, visceromegaly, a disproportional increase in abdominal circumference and omphalocele [5] .…”
Section: Discussionmentioning
confidence: 99%
“…Others have suggested that in the absence of maternal diabetes, an approach to the fetus with macrosomia, polyhydramnios and an enlarged placenta should include targeted ultrasound to examine for macroglossia, visceromegaly, a disproportional increase in abdominal circumference and omphalocele [5] . However, even multiple second trimester imaging modalities will not always yield a prenatal diagnosis of BWS when it occurs in the absence of omphalocele or a detectable abnormal fetal profile [4][5][6][11][12][13][14][15] . As summarized in table 2 , few nonspecific ultrasonographic findings are associated with BWS [5] .…”
Section: Discussionmentioning
confidence: 99%
“…Cryptorchidism [Pettenati et al, 1986;Nowotny et al, 1994;Benacerraf and Bromley, 1998] and reduced fecundity [Moutou et al, 1992] are among the clinical findings described in male BWS patients. Interestingly, ZNF214 and ZNF215 are predominantly expressed in the testis [Alders et al, 2000].…”
Section: Zinc Finger 214 and 215 Genesmentioning
confidence: 99%